QUALITY OF COMBINATION SILAGE OF BANANA STEMS WITH BUTTERFLY PEA (Clitoria ternatea) BASED ON ORGANOLEPTIC TEST - I M. D.T. A, Khristanta; Suryani, N. N.; Wirawan, I W. (Jurnal Peternakan Tropika, 2020)
The aim of this study was to determine the recommended level of Clitoria ternatea in terms of organoleptic test. This research was conducted at Sesetan Farm, Faculty of Animal Husbandry, Udayana University, Jl. Raya Sesetan, Markisa Alley, Denpasar. Organoleptic test was carried out at the Animal Nutrition and Feed Laboratory, Faculty of Animal Husbandry, Udayana University. The study design was a completely randomized design (CRD) with 4 treatments and 4 replications. Treatment A (65% banana stem + 30% polar + 5% (molasses + EM4)), B (55% banana stem + 10% C. ternatea + 30% polar + 5% (molasses + EM4)), C (45 % banana stem + 20% C. ternatea + 30% polar + 5% (molasses + EM4)), D (35% banana stem + 30% C. ternatea + 30% polar + 5% (molasses + EM4)). The research variables were pH, NH3, VFA, fungus, texture, color, and odor. Study showed that the highest color and odor values were obtained in treatment D, while the fungus and texture variables were the highest in treatment A. Addition of C. ternatea with levels of 20% and 30% (treatments C and D) show significant difference can increase NH3 compared to treatments A and B. Concentration of NH3 in treatment D compared treatments A, B and C respectively 327,50%, 407,92% dan 62,86%. The pH and total VFA did not show any significant difference between all treatment. The results of this study can be concluded that 30% C. ternatea can improve silage quality both in terms of NH3 as well as organoleptic test likes color and texture. Keywords : silage quality, banana steams, Clitoria ternatea, organoleptic test